DIGITALIZATION OF VOCATIONAL AND THEORETICAL TRAINING (Innovative professional education, 2023)
Digital technologies make life easier, optimizing routine processes, leveling borders in the educational space that goes beyond the borders of one's country and continent. Digitization is a reflection of the modern paradigm of the development of society, when competitiveness and efficiency appear as vitally necessary qualities. «Digitalization contributes to the simplification of the educational process, making it more flexible, adapted to the realities of the modern day, which ensures the formation of competitive professionals».
Keywords: professional education, digitalization, professionalism